Implementation of Assessment and Feedback in Higher Education - Elsayed, Shamira; Cakir, Define (Acta Pedagogia Asiana, 2023)
The ability of feedback to improve students' performance on a task, their techniques, and their learning has long been recognized in the literature. The primary goal of feedback is to reduce errors, close knowledge and skill gaps, and improve knowledge and skill acquisition. However, a student must use feedback to reach his or her full potential. Therefore, much of the recent feedback research has focused on examining student perceptions of feedback and how they relate to the effective use of feedback. This review provides a comprehensive overview of the literature on feedback perception. Inadequate theoretical frameworks, repetition (but not replication) of research, and methodological flaws in the articles reviewed have led to rather unsatisfactory conclusions. This type of feedback often does nothing to improve student learning experiences. It is time for professors to rethink the practice of commenting. They should move away from conventional methods of providing feedback to students. This study describes some contemporary methods of feedback that can ultimately help students improve their learning experiences. This can also contribute to the professionalization of teachers in higher education. Based on the findings, we propose a framework for further research on students' perceptions of feedback and many future directions for this topic.